Hoof Wall Cracks in Cattle - Jan K. Shearer (EDIS, 2007)
VM-169, a 3-page illustrated fact sheet by Jan K. Shearer, describes vertical and horizontal wall cracks as important disorders in cattle that are indicative of physiological change or complications of disease or other stressors. Published by the UF Department of Animal Science, August 2007.